Inferior Lateral Genicular Artery Injury during Anterior Cruciate Ligament Reconstruction Surgery - J. M. Lamo-Espinosa; R. Llombart Blanco; J. R. Valentí (Case Reports in Surgery, 2012)
We report a case of inferior lateral genicular artery (ILG) injury during anterior cruciate ligament (ACL) reconstruction surgery with lateral partial meniscectomy. This is a rare arthroscopy complication. A review of the literature has been made with the aim to define the anatomy of ILG across the lateral articular line and the risk of lesion during knee arthroscopy. We propose embolization as a good treatment option for this type of injuries.